Anaphylactic reaction: lesson learned from three cases - William Bunga Datu; Emita Raya Katinda; Andrew Suprayogi (DiscoverSys Inc., 2022)
Background: An anaphylactic reaction is an emergency that can be life-threatening if not recognized immediately. Signs and symptoms that appear vary from mild to severe. After knowing that it is an anaphylactic reaction, it needs immediate action and special attention, especially from general practitioners who work in the emergency unit. Case presentation: In this scientific publication, three cases will be presented, all of which were found in the emergency room at Cikarang Medika Hospital, Bekasi. These cases of anaphylaxis vary in the onset of signs and symptoms, clinical manifestation, allergen, degree of severity, and therapeutic response. However, in these three cases, the initial management, which was an emergency, was the same for each patient, and all cases occurred at home; thus, education on anaphylaxis in the general community is vital, especially for the patients and their families. Conclusion: As a physician who works in the emergency room is essential to know how to quickly recognize the signs and symptoms of an anaphylactic reaction and carry out treatment as soon as possible so that patients can be helped. The first line treatment is Epinephrine and other treatment may follow after the first line has been given. It is essential that the public needs to know about the occurrence, the cause or trigger, and first aid (what they should do in the event of an anaphylactic reaction).